The Role of Islamic Education on Parenting Patterns - Resa Zubaidah Resa; Tyas Nur Aulia; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
The family is the oldest educational institution, informal in nature, which is experienced first and foremost by children and natural educational institutions. Parents are responsible for nurturing, caring for, protecting, and educating children so that they grow and develop properly. The role of Islam in supporting the parenting of children. As for parenting according to Islam, it is carried out in several methods including through example, customs, advice, attention, and punishment.